The Role Of International Cooperation In Facing Environmental Security Threats (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The issue of achieving environmental security is one of the most important and serious issues facing the international community, since environmental damage can cross the temporal and spatial borders of countries and has serious effects on human health, food and all elements of his life, members of the international community have realized the seriousness of this damage and that there is a global need to confront threats to environmental security, so conferences were held and international agreements concluded to discuss issues and challenges that face achieving environmental security and to develop preventive and curative solution to problems that harm the environment. However, activating the effects of this international cooperation requires instilling a culture of concern for and protection of the environment among all members of society and its institutions and applying the principle of priority of environmental considerations over political and economic considerations in all countries, possession of the binding international mechanism capable of ensuring the implementation of international environmental obligations in order to preserve wealth and natural resources to achieve sustainable development, and reduce the risks of environmental problems that threaten environmental security in particular and human security in general.